2020
DOI: 10.5194/tc-14-2999-2020
|View full text |Cite
|
Sign up to set email alerts
|

Estimating statistical errors in retrievals of ice velocity and deformation parameters from satellite images and buoy arrays

Abstract: Abstract. The objective of this note is to provide the background and basic tools to estimate the statistical error of deformation parameters that are calculated from displacement fields retrieved from synthetic aperture radar (SAR) imagery or from location changes of position sensors in an array. We focus here specifically on sea ice drift and deformation. In the most general case, the uncertainties of divergence/convergence, shear, vorticity, and total deformation are dependent on errors in coordinate measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Following Lindsay and Stern (2003) and Dierking et al. (2020), we also consider σ geo =0 in the present study for RGPS, but we have verified that the results presented in section 4 are robust to considering a nonzero geolocation error within uncertainty (since the added error uniformly affects all deformation estimates). With the assumption of a zero geolocation error, the strain rate errors reduce to σtrueϵ˙112=truei=14)(false(yi+1yi1false)24A2T2σtrack2, σtrueϵ˙122=truei=14)(false(xi+1xi1false)24A2T2σtrack2, σtrueϵ˙212=truei=14)(false(yi+1yi1false)24A2T2σtrack2, σ…”
Section: Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…Following Lindsay and Stern (2003) and Dierking et al. (2020), we also consider σ geo =0 in the present study for RGPS, but we have verified that the results presented in section 4 are robust to considering a nonzero geolocation error within uncertainty (since the added error uniformly affects all deformation estimates). With the assumption of a zero geolocation error, the strain rate errors reduce to σtrueϵ˙112=truei=14)(false(yi+1yi1false)24A2T2σtrack2, σtrueϵ˙122=truei=14)(false(xi+1xi1false)24A2T2σtrack2, σtrueϵ˙212=truei=14)(false(yi+1yi1false)24A2T2σtrack2, σ…”
Section: Methodssupporting
confidence: 62%
“…Dierking et al. (2020) also suggested that the geolocation errors should be treated as biases affecting equally all points in a given SAR image given that variations in the orbit of the satellite is uniform across a given pass, such that σ geo =0. Following Lindsay and Stern (2003) and Dierking et al.…”
Section: Methodsmentioning
confidence: 99%
“…where y is the grid spacing in the y direction, i.e., 700 m. For a regularly spaced grid this calculation to derive deformation is identical to the commonly used equations for a combination of 2 × 2 adjacent velocity grid cells, which are based on Green's theorem. (see Supplement and, e.g., Kwok et al, 2003Kwok et al, , 2008Dierking et al, 2020). The velocity gradients were evaluated every 700 m, corresponding to a step width of one grid cell.…”
Section: Sea Ice Drift and Deformation From Sequential Sar Imagesmentioning
confidence: 99%
“…Convergent motion results in the closing of leads and then rafting and ridging of young and old ice. Ridging of thick ice forms pressure ridges that are many times thicker than the initial thickness (Strub-Klein and Sudom, 2012;Duncan et al, 2020). Ridging and rafting shape the ITD predominantly by redistributing thin ice to thicker ice categories (e.g., Thorndike et al, 1975;Wadhams, 1994;Rabenstein et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We discretized the curve applying the trapezoid method that linearly interpolates velocity between the vertices ( ) of the grid cells (e.g. Kwok et al, 2008;Dierking et al, 2020). The spatial derivatives are thus given by:…”
Section: Sea Ice Deformation Derived From Drift Fieldsmentioning
confidence: 99%